The role of gender equality on rural women development in agriculture : case study: koperative duhinge ikigori kanjongo “KODIKA”, Nyamasheke district, Rwanda - Mukakalisa, Christella (SLU/Dept. of Urban and Rural Development, 2021)
Gender is as a contract in society regulating the relations between men and women. But Gender equality is referred to as equal rights, roles and responsibilities for men and women. It is a crucial element in sustainable development, and it is considered as human rights. In Rwanda, Rural women’s development refers to things such as participating in private and public agricultural activities, necessary about changing the life of rural women in a positive manner. Productive agricultural activities are expected to generate incomes, food security and improve nutrition. In Rwanda, currently there is an important improvement in gender equality however higher workload including care duties, large number of women in agriculture, control over materials and financial income, and land are examples that have restrained women to development in the past years. The purpose of this thesis was to study gender equality in the context of rural agriculture development in a cooperative called KOPERATIVE DUHINGE IKIGORI KANJONGO “KODIKA”, in Nyamasheke District, Rwanda. In this thesis, research on gender equality based on the cooperative such as access to land, care duties in families, household’s agriculture activities, participation, division of labour, decision making, leadership and impacts of rewards on families from the cooperative are studied. It was found that most women are responsible for care duties and men as head of the family can help them sometimes such as during sickness. Moreover, household agricultural activities are divided on preference between men and women, but more women are found in seeding and weeping while men prefer jobs such as construction and transportation that can generate money daily. All participants in this study said that men and women have equal access to land and mostly they decide together on the usage of the rewards from the cooperative. In KODIKA, anyone can lead without restriction to election but many women still lack confidence to express their ideas. It is promising that regular training on gender and equality will enhance the agricultural production and the wellbeing of the KODIKA members.